2010
DOI: 10.1002/art.27328
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol inhibits chondrogenic differentiation of mesenchymal stem cells via nonclassic signaling

Abstract: Objective. We undertook this study to examine the effects of estradiol on chondrogenesis of human bone marrow-derived mesenchymal stem cells (MSCs), with consideration of sex-dependent differences in cartilage repair.Methods. Bone marrow was obtained from the iliac crest of young men. Density-gradient centrifugation-separated human MSCs proliferated as a monolayer in serum-containing medium. After confluence was achieved, aggregates were created and cultured in a serum-free differentiation medium. We added dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 46 publications
(49 reference statements)
1
43
0
Order By: Relevance
“…(30) While we cannot rule out the theoretical possibility of nontarget effects of the Neo cassette, the fact that others have observed similar effects on early osteoblast proliferation and suppression of chondrogenesis (proliferation was not specifically measured) using completely different systems gives us confidence in the fidelity of our results. (28,40) We should point out it also has been reported that the Cre-lox approach used by the other authors may result in unrecognized chromosomal rearrangements. (41) Whatever is the explanation for the phenotypic differences between the two models, it is clear from results of both groups that GPR30 is a critical receptor in regulation of the growth plate.…”
Section: Discussionmentioning
confidence: 88%
“…(30) While we cannot rule out the theoretical possibility of nontarget effects of the Neo cassette, the fact that others have observed similar effects on early osteoblast proliferation and suppression of chondrogenesis (proliferation was not specifically measured) using completely different systems gives us confidence in the fidelity of our results. (28,40) We should point out it also has been reported that the Cre-lox approach used by the other authors may result in unrecognized chromosomal rearrangements. (41) Whatever is the explanation for the phenotypic differences between the two models, it is clear from results of both groups that GPR30 is a critical receptor in regulation of the growth plate.…”
Section: Discussionmentioning
confidence: 88%
“…6). Expression of the genes CYP24A1 and MMP13 has previously been reported to be activated by estrogens [57, 58]. Thus, it is tempting to speculate that repression of ERβ - knowing to act as an ERα antagonist in certain settings - might increase estrogen-triggered expression of MMP13 and CYP24A1 mediated by ERα.…”
Section: Discussionmentioning
confidence: 99%
“…171 Although part of this effect is mediated through ERα and ERβ ,168 several avenues of research now suggest a role for GPER in bone and cartilage metabolism. In bone, GPER is expressed in osteocytes, osteoclasts and osteoblasts, 172,173 and is also detected in chondrocytes, 172,174 differentiation of which is regulated by GPER. 174 In addition, GPER expression also regulates bone growth, as illustrated by several models of GPER-deficiency, albeit in a sex-dependent manner.…”
Section: Gper In Physiology and Diseasementioning
confidence: 99%
“…In bone, GPER is expressed in osteocytes, osteoclasts and osteoblasts, 172,173 and is also detected in chondrocytes, 172,174 differentiation of which is regulated by GPER. 174 In addition, GPER expression also regulates bone growth, as illustrated by several models of GPER-deficiency, albeit in a sex-dependent manner. GPER deficieny inhibits bone growth in female mice; 77 similar results were reported in ovariectomized, estrogen-treated animals, 108 suggesting a role for GPER in estrogen-induced bone growth and development.…”
Section: Gper In Physiology and Diseasementioning
confidence: 99%